Breast Cancer Risk by Extent and Type of Atypical Hyperplasia: An Update from the Nurses’ Health Studies - Collins, Laura C. (Cancer, 2015)
BACKGROUND: Women with atypical hyperplasia (AH) on a benign breast biopsy (BBB) are at increased risk for the development of breast cancer. However, the relationship between type and extent of AH (atypical ductal hyperplasia (ADH) vs. atypical lobular hyperplasia (ALH)) and magnitude of breast cancer risk is not well-defined. METHODS: We conducted a nested case-control study of benign breast disease and breast cancer risk. Women with breast cancer and a prior BBB (cases=488) were matched to women with a prior BBB but free from breast cancer (controls=1907). BBB slides were reviewed and categorized as either non-proliferative, proliferative without atypia, or AH (ADH or ALH). The number of foci of AH was also recorded. RESULTS: Among women with ADH, the inter-relationship between extent of atypia and breast cancer risk was not significant (OR=3.5; 95%CI 2.2-5.6 for 1-2 foci, OR= 2.7; 95%CI 1.4-5.1 for ≥3 foci; p=0.58). Similarly, while the risk with ALH was higher for those with ≥3 foci than for those with <3 foci, the difference was not statistically significant (OR=5.2; 95%CI 2.7-10.0 for 1-2 foci; OR=8.0; 95%CI 4.5-14.2 for ≥3 foci; p=0.66). CONCLUSION: This analysis demonstrates that the extent of ADH or ALH did not significantly contribute to breast cancer risk. The lack of a significant dose-response relationship between extent and type of atypia and breast cancer risk suggests that it would be premature to use extent of atypia to influence management decisions in women with ADH or ALH.